Symbolic Meaning Relationship between the Condong Character and the Putri in the Gambuh Batuan Dance Drama - Ciclia Indraningsih Jeno; Ni Made Arshiniwati; Ida Ayu Trisnawati (Institut Seni Indonesia Denpasar, 2023)
Gambuh is the oldest Balinese theatrical dance drama, with a rich repertoire of dance movements, music, dramaturgy, and costume design, making it the source of Balinese performing arts that emerged later. The main story is about the journey of Prince Panji to find his lover, Princess Candra Kirana. There are two important female characters, namely Condong (servant) and Putri (Princess), who have different social statuses but have a close relationship and play a key role at the beginning of the drama, making them the determinant of the success of the performance. The research aims to reinterpret the meanings contained in the Gambuh dance drama, especially the relationship between Condong and Putri, to offer a living interpretation of local wisdom, pass them on to the next generations, and contribute to building the character of the nation that has nobility and refinement of character. The research was conducted using a qualitative research method, including a literature review, participatory observation, and in-depth interviews in Batuan Village, Gianyar Regency, Bali. The research process begins with a formal description of the characters, dance movements, costumes, and antawacana (dialogue), then the symbolic meaning analysis is carried out using Aesthetic Theory and HG Gadamer and Paul Ricoeur's Hermeneutics approach. The results of the study show that the relationship between the two characters, Condong and Putri, carries the meanings of dedication, sincerity, ethics, and the strength of women - values that are local wisdom but very relevant to women today. The elements of Rwa Bhineda, which are two opposing forces, Trihita Karana, which is harmony with nature, God, and humans, and the Hindu concept of Satyam Sivam Shundaram, which embodies ethical and pure values wrapped in beauty in the Gambuh dance drama - are the essence of Gambuh that is relevant to the present day, making it universal, transcending time and distance.